Памятная книжка Вятской губернии и адрес-календарь ... - Спасский Николай Александрович (1993)
Экземпляры: КР (19980731) / Инвентарный номер: мф504 / Сис.шифр: 63.3(2...) / Авт.знак: П 15 / ГРНТИ: 03 / ББК: 63.3(235.5)